Detection of CTX-M-type ESBLs Escherichia coli at Universiti Kebangsaan Malaysia Medical Centre (Bangladesh Journal of Medical Science, 2016)
Objective: To determine ESBLs and CTX-M-type ESBL-producing Escherichia coli at Universiti Kebangsaan Malaysia Medical Centre (UKMMC) by multiplex PCR.Materials and Methods: ESBL producing E. coli strains were confirmed by disk diffusion method. On the contrary, CTX-M-type ESBL-producing E. coli strains were confirmed by multiplex PCR.Results: Out of 554 collected E. coli isolates from UKMMC, 96 of these were detected as ESBL-producers. In 96 isolates, 76 viable strains were subjected to multiplex PCR for the detection of blaCTX genes. In which 70 (92.1%) were CTX-M-type ESBLs with the majority of CTX-M-1 group (77.1%), followed by CTX-M-9 group (21.4%) and one (1.4%) from CTX-M-2 group. Conclusions: CTX-M-type ESBLs were the predominant ESBL types isolated at UKMMC. CTX-M-1 and -9 groups were found in majority of the clinical isolates. Although phenotypic characteristics based on disk diffusion test provided similar results, however, molecular detection of genes of organisms is important for further epidemiological investigations.Bangladesh Journal of Medical Science Vol.15(2) 2016 p.257-261